Women working in the informal sector (Conditions, causes and effects of women's work in the informal sector) (City and countryside of Lattakia model) - Aljourani , Nibal (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
"Women working in the informal sector," the study aims to identify the conditions and problems of women working in the informal sector as well as the reasons for their work in this sector, and also aims to identify the future aspirations so as to improve their situation. To achieve this purpose, the study interviews women workers in the informal sector who are between the ages of 23-50 years old and work in the areas of production and services. The study sample consists of 20 women from different educational levels of living in the city and countryside of Latakia. The cases of the study are asked to answer questions about the status of their work, taking into account the pressures faced by working in the field work. Results of the study shows that women (case studies) contribute to improving their standard of living through their work in the informal sector as well as part of them suffer from problems and difficulties at work. It is also a finding of the study, the role of the aforementioned sector in achieving economic and social independence for worker women. The study results through a set of recommendations and proposals that can contribute to improving the conditions of worker women in the informal sector.